Motivación y su aporte al desarrollo de habilidades y destrezas en el área de matemática a estudiantes de la Unidad Educativa Emigdio Esparza Moreno cantón Babahoyo Provincia Los Ríos - Macías Herrera, Lilia Otilda (2015)
The education system pursues the formation of the student, to develop competencies and skills that allow them to develop as a citizen / a proactive / a society to which it belongs. This intervention can only take place within a framework of inter-relationships through communication, allowing you to share with members of their community. In the area of mathematics content favor the use of many resources to potentiate the development of skills as it has been found that it is much easier to use them as cumulative tasks and not be considered as a simple support material. The new education model proposes changes where the emphasis is on quality and warmth in education that allows students to be competent to function in all circumstances, so the educational process can not be outside of these changes thus the practice helps in different educational concepts and theories to solve problems and situations relating to teaching and learning. Hence, the present study the psychological, educational and methodological foundations that foster their development from the class as an essential axis of the learning process as well as examples of types of tasks that can be used by the teacher is.